The effects of sensory integration techniques on muscle tone in children after prenatal exposure to alcohol - Wilczyński, Jacek; Habik, Natalia; Wypych, Żaneta (Journal of Education, Health and Sport, 2018)
Background: Prenatal exposure to alcohol is the cause of Foetal Alcohol Syndrome (FAS). Alcohol exerts an especially negative effect on the central nervous system of an unborn child. Children with FAS frequently have problems with sensory integration. The objective of the study was an evaluation of the effectiveness of SI therapy in children with Foetal Alcohol Syndrome on the example of muscle tension. Methods: The study was conducted in 2012 at the Centre of Advanced Physiotherapy in Kielce, and covered a group of 20 children aged 4-5 who had a history of prenatal exposure to alcohol. The children systematically participated in a one-hour SI therapy session, once a week for the period of 6 months. Results: A high effectiveness of SI therapy was confirmed in children after prenatal exposure to alcohol based on the example of muscle tension (p<0.001). The positive effects of therapy were proved for the following tests: in prone extension position (p<0.001), in supine, flexed position (p<0.05), ATOS (p<0.001), STOS (p<0.001), the Schilder test (p<0.001) and trunk stabilization (p<0.001). Conclusions: The sensory integration technique exerts a beneficial effect on the normalization of muscle tone in children after prenatal exposure to alcohol.